CoZnAl catalysts for ethanol steam reforming reaction - Barroso, Mariana Noelia (2010)
The ethanol steam reforming was studied at 500 and 600 °C on CoZnAl catalysts with different Co loading (9 and 25 wt.%) and a Zn:Al atomic ratio nearly constant (Zn:Al @ 0.6). The catalysts were prepared by the citrate sol gel method and characterized by different techniques such as TG, BET, TPR, XRD, RAMAN and SEM-EDX. They were active in the ethanol steam reforming at atmospheric pressure in the temperature range studied, but with significant differences in their performance. High hydrogen selectivities, better than 80 %, were obtained on catalyst with high Co loading (25 wt.%). CO, CO2 and minor amount of CH4 were the only carbon products at 600 °C.